Ten‐Gram‐Scale Synthesis of FAPbX3 Perovskite Nanocrystals by a High‐Power Room‐Temperature Ultrasonic‐Assisted Strategy and Their Electroluminescence. Issue 4 (31st January 2020) - Dou, Yongjiang; Wang, Sheng; Zhang, Chengxi; Luo, Hongde; Li, Xiaomin; Wang, Haoran; Cao, Fan; Shen, Piaoyang; Zhang, Jianhua; Yang, Xuyong
Abstract: Metal halide perovskite nanocrystals (NCs) have shown significant potential in light‐emitting applications due to the unique luminous properties, such as high color purity, tunability, and solution processability. However, the large‐scale production of perovskite NCs with high‐quality for meeting the commercial applications is still a challenge. Herein, a facile room‐temperature synthesis of ten‐gram‐scale FAPbX3 (FA + = HC(NH2 )2 +, X = Br, or mixed halide system Cl/Br and Br/I) NCs by a high‐power ultrasonic‐assisted strategy and the electroluminescence for light‐emitting diodes (LEDs) is reported. The uniform high‐power radiation avoids the adverse effects caused by heating and stirring unevenness, and no inert gas is needed in the reaction process. Meanwhile, the room temperature reaction reduces the crystallization rate of the NCs, leading to the successful synthesis of ten‐gram‐scale high‐quality FAPbX3 perovskite NCs. The resulting NCs show size‐focus distribution and high photoluminescence quantum yields of 93%, and the adjustable photoluminescence spectra from 453 to 695 nm by manipulating halide compositions. Attributed to the acquired FAPbBr3 NCs, a high‐efficiency green LED with the maximum current efficiency of 61.3 cd A −1 and external quantum efficiency of 14.1% is also obtained. Abstract : A facile room‐temperature synthesis of ten‐gram‐scale FAPbX3 nanocrystals (NCs) by a high‐power ultrasonic‐assisted strategy and the electroluminescence for light‐emitting diodes is reported. The resulting NCs show size‐focus distribution, high photoluminescence quantum yields of 93%, and high‐efficiency green light‐emitting diode with the maximum current efficiency of 61.3 cd A −1 and external quantum efficiency of 14.1%.